The effect of weight management interventions that include a diet component on weight related outcomes in pregnant and postpartum women: a systematic review protocol - Spencer, L.; Rollo, M.; Hauck, Yvonne; Macdonald-Wicks, L.; Wood, L.; Hutchesson, M.; Giglia, Roslyn; Smith, R.; Collins, C. (2015)
Review question/objective: What are the effects of weight management interventions that include a diet component on weight-related outcomes in pregnant and postpartum women? The primary objective of this systematic review is to evaluate the effectiveness of weight management interventions which include a diet component and are aimed at limiting gestational weight gain and postpartum weight retention in women. The second objective of this systematic review is to investigate included intervention components with respect to effect on weight-related outcomes. This may include, but is not limited to: length of intervention, use of face-to-face counselling, group or individual consultations, use of other interventions components including exercise, use of goals and use of support tools like food diaries, coaching, including email or text message support.